Oral etoposide as first‐line therapy in the treatment of patients with advanced classic Kaposi's sarcoma (CKS): a single‐arm trial (oral etoposide in CKS). (20th December 2011) - Tas, F.; Sen, F.; Keskin, S.; Kilic, L.
Abstract Background Classic Kaposi's sarcoma (CKS) affects an elderly population; it is important to have effective treatment options with high activity and relatively low toxicity, and availability to be used for long periods. Objective We investigated the activity and safety of single‐agent etoposide with an oral administration schedule in patients with advanced CKS. Methods Histologically confirmed, CKS patients were eligible for study. All had a negative test for HIV and good performance status. All patients received oral etoposide 50 mg twice daily for 10 days every 3 weeks. Results Thirty patients (median age 66 and 22 males) were enrolled into the study. The majority of them had non‐metastatic, local advanced disease and symptoms in nearly half of patients. Complete and partial responses were observed in 10% and 77% of patients, respectively, giving an overall response rate of 87%. Stable disease occurred in the other 13% of patients. Treatment was well tolerated. Grade IV toxicity was not observed. Haematological toxicity was the principal dose‐limiting side effect. Severe leucopaenia and neutropaenia were observed in 7% and 10% of patients respectively. No patient was complicated by febrile neutropaenia. Mild‐moderate anaemia observed frequently, but only 3% of patients had severe anaemia and severe thrombocytopaenia was not observed. The 5‐year overall survival rate was 92%. Conclusions Single‐agent oral etoposide is an effective treatment option and is acceptably toxic and easily administered. Therefore, we recommend the single agent of oral etoposide as the first‐line chemotherapy for advanced CKS.